A Study On The Awareness Of The Malaysian Apparel Website - Low, Sandy Bee Choo (2007)
This study is a litmus test on Malaysians awareness on the local apparel sites. Some of the highlighted rationale to shop for apparels online is the experience, convenience and availability.